Abdominal access techniques (including laparoscopic access). Issue 5 (May 2018) - Merali, Nabeel; Singh, Sukhpal
Abstract: This article discusses the safe exposure of intra-abdominal organs using laparoscopy and laparotomy. Newer methods of minimal access surgery including single incision laparoscopic surgery (SILS), and natural orifice transluminal endoscopic surgery (NOTES) are also discussed. Common abdominal incisions are illustrated.